Environmental Risk Factors and Hookworm Infection among Schoolchildren in Rural Areas of Indonesia - Blego Sedionoto; Akhmad Azmiardi; Witthaya Anamnart (Journal of Epidemiology and Public Health, 2025)
Background: The prevalence of hookworm infection is a serious public health concern globally. Java Island and Kalimantan Island have differential environmental risk factors of hookworm infection, especially in rural areas of Indonesia, which have high-risk environmental factors for the prevalence of hookworm infection. This study aimed to investigate the infection rates and correlation between environmental risk factors and the prevalence of hookworm infection. Subjects and Method: This was a cross-sectional study conducted among 226 school children from rural East Java province, Central Java Province, and East Kalimantan Province, Indonesia. A simple random sampling method was applied to select participants from each school area. This study used two diagnostic methods: Kato Katz and Koga agar plate culture/KAP culture for diagnosing hookworm infections. Environmental variables examined included soil texture, organic carbon content, clay content, soil pH, rainfall volume, number of rainy days, humidity, temperature, elevation, vegetation type, and pet infection status. Pearson's chi-square analysis was used to study the correlation between environmental factors and hookworm infection. Results: Hookworm, Strongyloides sp, and Ascaris sp infections were found in this study; 137 (60.63%), 25 (11.1%), and 124 (9.84%), respectively. Environmental risk factors such as rainy season, quality of soil, and infection with hookworm in pets have a significant correlation (p<0.050) with hookworm infection among schoolchildren in a rural area in Indonesia. Conclusion: The prevalence of hookworm infection correlates with environmental factors, and the findings in this research could contribute to decreasing the prevalence of hookworm infection, especially among schoolchildren in rural areas.